Identifying the Impact of New Digital Infrastructure on Urban Energy Consumption: Evidence from the Broadband China Strategy - Xianpu Xu; Qiqi Meng; Jing Huang (Energies)
China aims for high-quality development by balancing energy use and economic growth, leveraging digital infrastructure to foster a resource-efficient, eco-friendly society and boost economic progress. In this context, by using panel data from 279 Chinese cities spanning 2006–2021, this study employs a multi-phase difference-in-differences (DID) technique to disclose how the Broadband China Pilot Policy (BCPP) affects energy consumption. The results reveal that the BCPP can greatly lower urban energy consumption, which is further validated by robustness tests, including PSM-DID estimation, Bacon decomposition, and placebo testing. Heterogeneity testing shows the BCPP significantly lowers energy consumption in large, eastern, non-resource-based, and high-digital inclusive finance cities compared to smaller, western, resource-based, and low-digital inclusive finance cities. Furthermore, the mechanism analysis indicates that the BCPP contributes to decreased urban energy use by transforming the industrial structure, enhancing financial growth, and improving green technology innovation. To effectively harmonize energy consumption with urban development, it is recommended to accelerate the advancement of digital infrastructure, tailor the industrial structure to meet local needs, and promote greater financial and green innovation development.